Effect of Er:YAG laser irradiation and chitosan biomodification on the stability of resin/demineralized bovine dentin bond - Curylofo-Zotti, Fabiana Almeida; Scheffel, Débora Lopes Salles [UNESP]; Macedo, Ana Paula; Souza-Gabriel, Aline Evangelista de; Hebling, Josimeri [UNESP]; Corona, Silmara Aparecida Milori (My University, 2019)
Objective: The purpose of this study was to evaluate the effect of Er:YAG laser for selective removal of carious lesion, followed by biomodification with chitosan on the microtensile bond strength (µTBS), adhesive interface, dry mass loss and hydroxyproline release (HYP). Methods: Artificial lesions were created in 104 bovine dentin blocks. Blocks were divided according to caries removal method: bur or Er:YAG laser. Seventy-six blocks were acid etched and subdivided according to dentin biomodification: no chitosan and 2.5% chitosan. Composite resin restorations were performed. Blocks were sectioned into beams and stored in water. After 24 h, 6 and 12 months, beams were submitted to μTBS test (n = 10) and analysis of adhesive interface by SEM (n = 3). The other 28 blocks were sectioned into beams and initial dry mass (DM) was determined (n = 7). Beams were stored and after 7 days, DM was redetermined. HYP release (n = 7) was evaluated by ELISA. Data were analyzed by ANOVA and Bonferroni's tests (α = 0.05). Results: After 24 h, the highest µTBS was found for bur (p < 0.001). After 6 months, methods were similar (p = 0.432). After 12 months, laser-irradiated dentin showed the highest µTBS values (p = 0.025). Chitosan promoted higher µTBS values after 6 (p = 0.011) and 12 months (p < 0.001) preserving adhesive interface. Dry mass loss and HYP release were not influenced (p > 0.05) by caries removal method or by dentin biomodification. Conclusion: The bond strength to demineralized dentin reduced over 50% in all groups after water storage. From 6 months of water storage, Er:YAG laser irradiation and biomodification with chitosan maintained the stability of the resin-dentin bonds, but did not influence dry mass loss and HYP release.
Keywords: Collagen; Demineralized dentin; Hydroxyproline; Lasers; µTBS